Development of a surface cryogenic propellant transfer concept for Martian operations. Issue 1 (1st May 2022) - Congiardo, J; Krenn, A; Martinez, J; Dupuis, M; Swanger, A
Abstract: NASA is currently evaluating architectures to support human missions to Mars. A multitude of concepts are being traded and associated sensitivities are being analyzed. Mars Ascent Vehicle (MAV) propellant supply is a key consideration. Mass constraints for the Mars descent system and in-space transportation present significant architectural challenges that may preclude landing a fully fueled MAV for crew use. In such a case, to ensure the ability of the crewed mission to meet its objectives, propellant should be supplied to the MAV prior to the arrival of the crewed mission from Earth. A concept to robotically transfer liquid oxygen from a separate storage tanker across the surface to the MAV is proposed. This concept makes use of an unpressurized rover and is optimized to maximize the amount of propellant conveyed per trip.